MUI PUBLIC COMMUNICATION STRATEGY IN SOCIALIZATION SINOVAC VACCINE HALAL IN INDONESIA - Bambang Afrianto; Mailin Mailin (Universitas Dharmawangsa, 2021)
ABSTRACT The spread of the Covid-19 virus, which is still worrying in Indonesia, has caused the government to take steps to provide vaccines, to suppress and prevent the negative impacts that arise. Since early 2021, the government has started using the Sinovac vaccine, which is produced by Bio Farma (Bandung, Indonesia), in collaboration with Sinovac Biotech Inc (Beijing, China). However, there was a reaction in the form of issues that discredited the vaccine, especially related to its halalness, and finally, the Indonesian Ulema Council issued a fatwa on the halalness of the vaccine to convince Muslims and other people. The method used for this paper is a content study by conducting a review of several literacies obtained from the main sources of MUI social media accounts. Furthermore, the fatwa on the halalness of vaccines socialized by MUI through various media also received responses from readers. At the MUI website address, the news about the halalness of the Sinovac vaccine received 10.7 k views and 1.9 k shares. Through Kompas TV media which was uploaded to the youtube channel, the news was watched 27.179 thousand times, got 193 likes, 10.8 million subscribers, and 228 comments. On CNN Indonesia the news was also watched 76,169 times, with 649 likes, 8.7 million subscribers, and 1,049 comments. Support for the video was also uploaded by LPPOM MUI which was divided into 2 episodes. Episode 1 was watched 14 times with 3.92 thousand subscribers and episode 2 was watched 15 times with 3.92 thousand subscribers. On the Facebook account, the news got 15 likes, 18 comments, and was shared 32 times, while on the Twitter account the news got 22 answers, 92 likes, and 5o retweets. The news has been retweeted 43 times for the android version, getting 7 quotes and 92 likes. Another strategy is to use the role of the da'i in the regions and give an example directly to the public by making Mr. President Joko Widodo the first person to be given the Sinovac vaccine. Keywords: Halal Vaccine. Sinovac, Vaccine Socialization, MUI Communication Strategy,